Creating a new seminar courses: Making magical one-credit courses - Powell, Charissa; Coleman, Tara L. (My University, 2021)
One-credit classes can be instrumental to a student’s success. Join two adjunct faculty librarians as they share their best practices for developing brand new one-credit first-year experience seminars. Planning a seminar course can be an exciting and challenging experience for both experienced instructors as well as novices. This presentation will provide information to those interested in teaching a new course for the first time and are unsure where to start. Attendees will leave this session knowing more about the needs of students, the right workload for a one-credit class, and how to make classes meaningful and valuable to students.